DETERMINAN KEJADIAN ANEMIA GIZI BESI PADA IBU HAMIL KURANG ENERGI KRONIS DI WILAYAH KERJA PUSKESMAS SUMBERJAMBE KABUPATEN JEMBER - Irwanti, Leilya; Sulistiyani, Sulistiyani; Rohmawati, Ninna (Jurnal Ilmu Kesehatan Masyarakat, 2019)
The iron deficiency anemia is a condition caused by a lack of nutrients that an important role in the formation of hemoglobin, it is happened due to the lack of consumption and due to absorption disorders. One of the factors associated with iron deficiency anemia in pregnant women is chronic energy deficiency. This study aimed to examine the determinants of the incidence iron deficiency anemia in pregnant women with chronic energy deficiency in the working area of Sumberjambe Primary Health Center in Jember Regency. This research was a descriptive study. The determination of the sample in this study used a total sampling technique, there were 44 research subjects of pregnant women with chronic energy deficiency. The researcher collected the data by using interview methods, knowledge tests, and hemoglobin measurements of pregnant women. The results of the study show that most of pregnant women were in the young age group (20 years below), they had basic education level, unemployed, the family income is below the regional minimum wage of Jember, and had sufficient knowledge, had a low parity, low birth gap, ANC meets K4, most of their carbohydrates, proteins and fats consumption tend to be high. Meanwhile, the ironconsumption was in the deficit category. In the consumption pattern of iron inhibitors, most of them never consume tea, coffee, potatoes and they often consume long beans and cucumbers.